A Simple Elemental Sulfur Reduction Method for Isotopic Analysis and Pilot Experimental Tests of Symmetry‐Dependent Sulfur Isotope Effects in Planetary Processes. (24th June 2020) - Lin, Mang; Thiemens, Mark H.
Abstract: Recent insights into fundamental mechanisms underlying quadruple stable sulfur isotope ( 32 S, 33 S, 34 S, and 36 S) mass‐independent fractionation (S‐MIF) chemistry and potential implications for planetary processes highlight the urgent need of conducting laboratory experiments to delineate the chemical physics of S‐MIF. Elemental sulfur (S 0 ), a ubiquitous component in the atmospheres of early Earth and Mars, is a major product or reactant in most experiments. Developing different chemical protocols for isotopic analysis is consequently of utility. The reduction of S 0 to hydrogen sulfide (H2 S) is the first step of the fluorination method for isotopic analysis, but existing S 0 reduction methods require relatively long chemical reagent preparation time. Here we present an operationally simple and rapid method for reducing S 0 to H2 S directly by "Thode solution." External uncertainties of our method for δ 34 S, Δ 33 S, and Δ 36 S measurements (associated with reduction, fluorination, purification, and mass spectrometer analysis) are 0.3‰, 0.01‰, and 0.2‰, respectively, comparable with traditional methods. This new technique was used to determine quadruple stable sulfur isotope compositions of product S 0 in a set of pilot experiments designed to investigate possible symmetry‐dependent isotope effects in planetary‐relevant elemental sulfur recombination reactions. Differences in Δ 33 S and Δ 36 S between initial and produced S 0 are slightly larger than analytical errors, shedding new light into the role of sulfur recombination reactions in S‐MIF. Our study offers a practical approach for measuring multiple isotopic compositions of S 0 in laboratory and natural samples and creates new opportunities for deepening understanding of S‐MIF signatures in Archean rocks and Martian meteorites. Plain Language Summary: Quadruple stable sulfur isotope analysis ( 32 S, 33 S, 34 S, and 36 S) of elemental sulfur (S 0 ) using the fluorination method and isotope ratio mass spectrometer is useful for deepening understanding of biogeochemical and cosmochemical processes. We outline a new protocol for the chemical pretreatment of S 0 using a mixture of hydriodic acid, hypophosphorous acid, and hydrochloric acid. The new protocol eliminates time‐consuming works of preparing or purifying chemical reagents and offers a new avenue for rapid isotope analysis of S 0 produced from laboratory experiments and extracted from natural samples. We examined the applicability of our new method on S 0 produced in a set of pilot chemical physics experiments relevant to planetary processes such as impact events and volcanoes. The results highlight the applicability of this new technique and an urgent need of understanding fundamental mechanisms of sulfur isotope effects in various planetary processes. Key Points: A simple elemental sulfur reduction method was developed for quadruple sulfur isotopic analysis The external uncertainties of the new method are comparable with traditional methods Pilot experimental tests of isotope effects in sulfur recombination reactions were carried out as an application example of the new method